The Principle of Contributory Capacity as the Foundation of the Financial Constitution A Doctrinary and Jurisprudential View - Tarsitano, Alberto (2014)
The content and function of the contribution capacity principle has been a controversial issue for economists and jurists. Through the jurisprudence of the Constitutional Court of Peru, the author claims the capacity of contribution as an implied constitutional principle to award a self-governing function from other principles (legality, equality and non confiscatory) and recognize the outstanding methodological contribution to the Financialand Taxation law unit.